Pengaruh Kebijakan Efisiensi sebagai alasan Penjatuhan PHK: Perbandingan antara Undang-Undang Ketenagakerjaan dan Undang-Undang Cipta Kerja - Kerenhapukh Milka Tarmadi Putri; Gunardi Lie (Syntax Literate, 2023)
Termination of employment (PHK) is a serious action that is often taken by employers for various reasons. Economic pressure, market competition, or strategic changes are often the justification for companies to make efficiency by laying off workers so that the company can survive. These reasons often trigger inequality of power between employers and workers, which in turn can result in many workers' rights being violated. This is further triggered by the renewal of the regulation of the Manpower Law. Initially, this law stipulated that companies could conduct layoffs on the grounds of efficiency with the requirement that the company close. But now these requirements have changed as outlined in the Undang-Undang Cipta Kerja. Undang-undang Cipta Kerja adds a new reason that companies can carry out layoffs for efficiency reasons without the condition that the company closes, but only on the grounds of experiencing losses or even just to prevent losses from occurring. This change in requirements expands the freedom of employers to be able to lay off workers. Therefore, effective legal and regulatory protection plays a very important role in ensuring that workers still have rights and interests that must be respected when the company conducts layoffs. In this research, the author wants to further examine the rights of workers when layoffs are carried out for efficiency reasons. the research method used is normative juridical which is carried out on library materials / secondary data consisting of primary legal materials, secondary legal materials and non-legal materials. The research approach used in this research is a statutory approach. This approach is used to examine the applicable rules/regulations regarding employment, especially regarding layoffs for efficiency reasons.